Inflammation and the Intestinal Barrier: Leukocyte–Epithelial Cell Interactions, Cell Junction Remodeling, and Mucosal Repair - Luissint, Anny-Claude (Gastroenterology, 2016)
The intestinal tract is lined by a single layer of columnar epithelial cells that forms a dynamic, permeable barrier allowing for selective absorption of nutrients, while restricting access to pathogens and food-borne antigens. Precise regulation of epithelial barrier function is therefore required for maintaining mucosal homeostasis and depends, in part, on barrier-forming elements within the epithelium and a balance between pro- and anti-inflammatory factors in the mucosa. Pathologic states, such as inflammatory bowel disease, are associated with a leaky epithelial barrier, resulting in excessive exposure to microbial antigens, recruitment of leukocytes, release of soluble mediators, and ultimately mucosal damage. An inflammatory microenvironment affects epithelial barrier properties and mucosal homeostasis by altering the structure and function of epithelial intercellular junctions through direct and indirect mechanisms. We review our current understanding of complex interactions between the intestinal epithelium and immune cells, with a focus on pathologic mucosal inflammation and mechanisms of epithelial repair. We discuss leukocyte–epithelial interactions, as well as inflammatory mediators that affect the epithelial barrier and mucosal repair. Increased knowledge of communication networks between the epithelium and immune system will lead to tissue-specific strategies for treating pathologic intestinal inflammation.